2012
DOI: 10.1371/journal.pone.0046257
|View full text |Cite
|
Sign up to set email alerts
|

Severe Loss of Suitable Climatic Conditions for Marsupial Species in Brazil: Challenges and Opportunities for Conservation

Abstract: A wide range of evidences indicate climate change as one the greatest threats to biodiversity in the 21st century. The impacts of these changes, which may have already resulted in several recent species extinction, are species-specific and produce shifts in species phenology, ecological interactions, and geographical distributions. Here we used cutting-edge methods of species distribution models combining thousands of model projections to generate a complete and comprehensive ensemble of forecasts that shows t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
0
6

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(35 citation statements)
references
References 31 publications
2
27
0
6
Order By: Relevance
“…A common approach to explore the location of climatically suitable areas in the future (Garcia et al 2012;Loyola et al 2012) involves the use of Ecological Niche Models (ENMs; also called Species Distribution Models -but see Araújo & Peterson (2012) and Peterson & Soberón (2012)). These individualistic responses of species' geographical range and from variation through time.…”
Section: Introductionmentioning
confidence: 99%
“…A common approach to explore the location of climatically suitable areas in the future (Garcia et al 2012;Loyola et al 2012) involves the use of Ecological Niche Models (ENMs; also called Species Distribution Models -but see Araújo & Peterson (2012) and Peterson & Soberón (2012)). These individualistic responses of species' geographical range and from variation through time.…”
Section: Introductionmentioning
confidence: 99%
“…G i is the number of species gained in the cell i. L i is the number of species lost, and SR i is the current species richness found in the cell [75]. Species turnover rate can measure the dissimilarity between the current and future species composition [76], and often regarded as a good proxy of community structure in the assessment of potential impacts of climate change [77].…”
Section: Assessing Climate Change Influencementioning
confidence: 99%
“…When predicting climate change effects on species distributions, commission errors lead to overestimation of range expansions whereas omission errors produce overestimates of range contractions. If one is employing such models to predict regions of climatic stability (Garcia et al 2012;Loyola et al 2012;Terribile et al 2012), and to guide conservation actions, both omission and commission errors are of particular interest, as these errors are likely to produce huge bias in the results of gap-analysis as well (Marini et al 2009). …”
Section: Turbine Modelsmentioning
confidence: 99%
“…It has been recently suggested that the use of ensemble of forecasts is preferred as oppose to model species distribution based on only one ENM (e.g. MaxEnt) (Loyola et al 2012). Ensembles of model projections keep only the consensus-projected areas, minimizing variation among all projections (Araújo & New 2007).…”
Section: Turbine Modelsmentioning
confidence: 99%